SUSTAINABILITAS PENGUSAHA KERAJINAN GERABAH DALAM BINGKAI KEMISKINAN STRUKTURAL: (Studi Pada Desa Ouw Kecamatan Saparua) - Ludwina Pormes; Audry Leiwakabessy (Jurnal Administrasi Terapan, 2023)
Ouw Village is a one of the potential Village in Saparua sub-district, Central Maluku Regency. They are famous for their pottery crafts since the ancient times. However, their business did not have an experience significant development and the craftsmen are still classified as a poor society. The purpose of this research is to know the effect of structural poverty on the sustainability of pottery craftsmen in the Ouw Village. This research use descriptive qualitative method with ethnographic techniques. The results show that structural poverty affects the sustainability of the pottery business in Ouw Village due to several factors including: unbalanced regulations, product distribution channels, lack of promotion and lack of funds for business development.Keywords: sustainability, structural poverty